Hydrocarbon generation potential and thermal maturity of Middle Jurassic Sargelu Formation in Miran Field, Sulaimani Area, Kurdistan Region, NE Iraq - Fatah, Sardar S.; Mohialdeen, Ibrahim M.J. (Sulaimani Journal for Pure and Applied Sciences, 2016)
The total 61 unwashed cutting rock samples of Sargelu Formation from both Miran-3 (M-3) and Miran-4 (M-4) wells have been investigated in this study. The area of interest is Miran Field; which locates in the High Folded Zone, about 30 Km Northwest of Sulaimani City, Kurdistan region, NE of Iraq. The samples have been tested by Rock- Eval Pyrolysis and Vitrinite reflectance in order to determine organic richness, hydrocarbon potentiality, types of organic matter, and thermal maturity level of the Sargelu Formation in Miran Field. The Total Organic Carbon content (TOC wt. %) for the Sargelu Formation ranged from 0.99-6.56 wt. %, average 2.23 wt. % for M-3 well, and between 0.86-6.41 wt. %, average 2.74 wt. % for M-4 well. It considered as a very good source rock based on TOC wt. % content. The data reveals that this formation in both wells has low amounts of Hydrogen Index (HI) (average 58, and 68 mg HC/g TOC for M-3 and M-4 wells, respectively), low amounts of S2 (average 1.28, and 1.44 mg HC/g Rock for M-3 and M- 4, respectively), as well as low amounts of Pyrolysable carbon (PC wt. %). While, the samples have high value of Residual Carbon (RC wt. %). Thus, the Sargelu Formation has low potentiality and it is classified as a poor to fair source rock for releasing hydrocarbons. According to the interpretation of the Rock-Eval data, the kerogen types of Sargelu Formation are mostly admixture between type II and type III kerogen. This result is also supported by microscopical approach, which indicating that the dominant organic matter populations within the samples are solid bitumen. However, the ability of Sargelu Formation is only remain for gas generation in the studied field. The analyzed samples reveal high values of thermal maturity based on the values of equivalent vitrinite reflectance (eq.VRo %). The value of eq.VRo% is between 1.5%- 1.55% for M-3 well and between 1.4%-1.45% for M-4 well, which indicate postmature; i.e. gas generation zone. Whereas, peak mature is assigned based on the production index (PI) parameter (average of PI is 0.33 and 0.27 for M-3 and M-4 wells, respectively). Maturity assessment bases on Tmax is not applicable in this study, because of the effects of mud additives, therefore this parameter is not depending for the maturity assessment of the studied formation.
Keywords: SargeluFormation; Kurdistan,Hydrocarbonpotentiality; Solidbitumen; ThermalMaturity